2012
DOI: 10.1007/s00330-012-2638-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the layering pattern of the apparent diffusion coefficient (ADC) for differentiation of radiation necrosis from tumour progression

Abstract: The three-layer pattern of ADC shows high specificity in diagnosing radiation necrosis; therefore, combined analysis of the ADC pattern with rCBV may have added value in the correct differentiation of tumour progression from radiation necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 24 publications
3
40
1
Order By: Relevance
“…12,23 Other articles have applied ADC histogram analysis 24 and 3-layer patterns of ADC analysis, 25 though these techniques are not commercially available and have not been incorporated into clinical practice. ADC may be decreased with treatment-related changes, possibly due to cellular inflammatory factors and abundant polymorphonuclear lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…12,23 Other articles have applied ADC histogram analysis 24 and 3-layer patterns of ADC analysis, 25 though these techniques are not commercially available and have not been incorporated into clinical practice. ADC may be decreased with treatment-related changes, possibly due to cellular inflammatory factors and abundant polymorphonuclear lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that if rCBV larger than 2.6 was used to differentiate radiation necrosis and tumor progression, the sensitivity was 100% but specificity was only 56%. If the lesions with moderately increased rCBV (2.6–4.1) were excluded from tumor progression, the sensitivity and specificity increased to 100% [88]. …”
Section: Investigational Imaging Techniques For Distinguishing Progrementioning
confidence: 99%
“…Subtraction maps were first developed two decades ago 22,23 , but their application in HGG has not been adopted. More recent advances, such as PWI, have improved surveillance and continue to be investigated with multiparametric approaches showing particular promise 24,25 . PWI was not acquired routinely on patients included in this study, but future analyses would benefit from the addition of this modality.…”
Section: Discussionmentioning
confidence: 99%